Balancing the Benefits and Risks of SGLT2 Inhibitors: Koristi in pasti zdravljenja s SGLT-2 zaviralci - Forštnarič, Alex; Stajan, Ana; Piko, Nejc (Acta Medico-Biotechnica, 2026)
Cardiovascular, renal, and metabolic diseases frequently coexist and are leading contributors to global morbidity and mortality. Sodium–glucose cotransporter 2 inhibitors (SGLT2is), originally developed for the treatment of type 2 diabetes mellitus, have demonstrated substantial benefits extending beyond glycemic control. This review synthesizes current evidence on the renal, cardiovascular, and metabolic effects of SGLT2is and highlights key clinical outcome trials supporting use.SGLT2is restore tubuloglomerular feedback, reduce intraglomerular pressure, and attenuate glomerular hyperfiltration by inhibiting sodium–glucose reabsorption in the proximal renal tubule, thereby slowing the progression of chronic kidney disease. Large randomized controlled trials have consistently demonstrated reductions in kidney disease progression, hospitalization for heart failure, and cardiovascular mortality in populations with and without diabetes. In addition, SGLT2is exert systemic effects, including modest reductions in body weight and blood pressure, improved metabolic efficiency, and modulation of inflammatory and oxidative stress pathways.Adverse effects, including genitourinary infections, volume depletion, transient declines in renal function, and rare events, such as diabetic ketoacidosis and Fournier’s gangrene, are also discussed.In summary, SGLT2is represent a transformative therapeutic strategy with broad, multi-system benefits across cardiovascular, renal, and metabolic diseases.
Keywords: SGLT2 inhibitors; type 2 diabetes; chronic kidney disease; heart failure; clinical outcomes